The integral ∫ 0 1 0 0 ⌊ arctan x ⌋ d x can be expressed as α − tan ( β ) . What is α + β ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes this how I wanted it to get solved .You did it @Milly Choochoo
We will split the integral into two parts :
I = ∫ 0 t a n ( 1 ) ⌊ t a n − 1 ( x ) ⌋ d x + ∫ t a n ( 1 ) 1 0 0 ⌊ t a n − 1 ( x ) ⌋ d x
Now for 0 ≤ x ≤ t a n ( 1 )
⇒ 0 ≤ t a n − 1 ( x ) ≤ 1
⇒ ⌊ t a n − 1 ( x ) ⌋ = 0
Also for t a n ( 1 ) ≤ x ≤ 1 0 0
⇒ 1 ≤ t a n − 1 ( x ) ≤ t a n − 1 ( 1 0 0 ) ≤ 2
⇒ ⌊ t a n − 1 ( x ) ⌋ = 1
⇒ I = ∫ 0 t a n ( 1 ) 0 d x + ∫ t a n ( 1 ) 1 0 0 1 d x
I = 1 0 0 − t a n ( 1 )
⇒ α = 1 0 0 , β = 1
α + β = 1 0 1
Nice,used same method.
Just integrate it directly, as follows
∫ 0 1 0 0 ( − 2 1 + A r c T a n ( x ) − 2 π 1 i L o g ( − e − 2 i π A r c T a n ( x ) ) ) d x =
1 0 0 − T a n ( 1 )
ta-da!
OOPS! it's not " 1 0 0 − arctan 1 "!
Log in to reply
Oh, sorry, typo. Changed it from ArcTan(1) to Tan(1). Thankee. But it doesn't change the integral. There's a method for directly integrating the floor of a function.
Obviously, if ArcTan(x)=1, where x is the jump, then Tan(1)=x. Doh!
0 ∫ 1 0 0 ⌊ tan − 1 x ⌋ d x = 0 ∫ tan 1 ⌊ tan − 1 x ⌋ d x + tan 1 ∫ 1 0 0 ⌊ tan − 1 x ⌋ d x = 0 ∫ tan 1 0 d x + tan 1 ∫ 1 0 0 1 d x = 1 0 0 − tan 1 ≈ 9 8 . 4 4 2 5 9 0 ∫ 1 0 0 ⌊ tan − 1 x ⌋ d x = 1 0 0 − tan 1 c
Problem Loading...
Note Loading...
Set Loading...
If you realize that arctan ( x ) is never more than 2 π ≈ 1 . 5 7 0 7 . . . , this problem is very easy.
So the integral is just the area of the box, which has a length 1 0 0 − tan ( 1 ) and height 1 . So the area is just 1 0 0 − tan ( 1 ) , so α + β is 1 0 1 .